STUDY ON PEST COMPLEX AND CROP DAMAGE IN MAIZE IN MEDIUM ALTITUDE HILL OF MEGHALAYA - PATRA, SANDIP; Z. RAHMAN; P. BHUMITA; K. SAIKIA; N.S. AZAD THAKUR (The Bioscan, 2013)
The experiment was conducted during 2010 and 2011 at ICAR Research Complex for North Eastern Hill Region, Umiam, Meghalaya to study the pest complex and assess their damage in maize. Maize variety, ‘Vijay composite’ was sown in the month of April during both the years in Randomized Block Design (RBD) with three replications. Two alternate middle rows out of seven rows in each plot were selected for taking observation. Total twenty four insect pests and some natural enemies including seven coccinellid beetles and two predatory bugs and thirteen spider species were recorded in maize. Among these, stem borer (Chilo partellus Swin.), cob borer (Stenachroia elongella Hamp.) and shoot fly (Atherigona soccata Rond.) were found to be as major pests, seventeen insects as minor pest and others considered as stray pests. Crop damaged by major pests were estimated at 8.5 and 21.75% by shoot fly, 15.67 and 13.45% by stem borer and 11.95 and 6.5% by cob borer during 2010 and 2011, respectively.